2015
DOI: 10.1016/j.sbspro.2015.04.897
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intention, Entrepreneurial Orientation of Faculty and Students towards Commercialization

Abstract: The present study is conducted to find out the entrepreneurial intention and entrepreneurial orientation of faculty and students towards commercialization of research. The study is conducted on a sample of respondents belonging to one research university of Malaysia. The results indicate that entrepreneurial orientation of faculty and students is having more influence towards commercialization of research than entrepreneurial intention alone. The results also indicate that the faculty and students are having a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
2
39
1
2
Order By: Relevance
“…parents, family, friends, network, the greater the 74 student's intention to be entrepreneurial. Camelo-Ordaz et al, (2016) consider entrepreneurial 75 self-efficacy, a concept derived from Social Learning Theory (SLT), whilst others have 76 described this characteristic as entrepreneurial orientation (EO), see Ishmail et al, (2015). shown to be weaker in females (Karimi et al 2013), but other studies have not found a gender 82 influence more generally in perceptions of entrepreneurship (Obeme et al 2014).…”
Section: Factors That Influence Student Entrepreneurialism 40mentioning
confidence: 99%
“…parents, family, friends, network, the greater the 74 student's intention to be entrepreneurial. Camelo-Ordaz et al, (2016) consider entrepreneurial 75 self-efficacy, a concept derived from Social Learning Theory (SLT), whilst others have 76 described this characteristic as entrepreneurial orientation (EO), see Ishmail et al, (2015). shown to be weaker in females (Karimi et al 2013), but other studies have not found a gender 82 influence more generally in perceptions of entrepreneurship (Obeme et al 2014).…”
Section: Factors That Influence Student Entrepreneurialism 40mentioning
confidence: 99%
“…In this case proactiveness, competitiveness and learning orientation were significant predictors of self-efficacy that was experimentally confirmed in a study of students' entrepreneurial orientation [1, p.6]. Entrepreneurial orientation in combination with sufficient level of entrepreneurial intentions may additionally contribute to the practical commercialization and educational products development, as already noted above [17]. We have suggested that the formation of some entrepreneurial skills of students within creative workshop "Geo-S» carry out as part of ESE development with deferred EI of graduates.…”
Section: Background and Research Methodologymentioning
confidence: 56%
“…Thirdly, EI is indicated as a goal in the formation of ESE, as it has the greatest impact on the effectiveness of the entrepreneurial behavior of graduates. It can be also significant to combinate EI and entrepreneurial orientation for commercialization in educational organizations of vocational training [17]. A number of researchers in engineering education note that students of technical universities initially have little business intention [3].…”
Section: Research In Entrepreneurship In Vocational Trainingmentioning
confidence: 99%
“…Logical components which are social, instructive and auxiliary help are considered as precursors of individual state of mind and saw conduct control, consequently they are required to affect entrepreneurial goal. The outcomes of Ismail et al, (2015) demonstrate that entrepreneurial introduction of staff and understudies is having more impact towards commercialization of research than entrepreneurial expectation alone. The examination adds to the current assemblage of writing identified with enterprise and the idea of entrepreneurial college.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our outcomes give valuable ramifications to strategy producers and teachers. Ismail et al, (2015) examination is directed on an example of respondents having a place with one research college of Malaysia. The outcomes demonstrate that entrepreneurial introduction of staff and understudies is having more impact towards commercialization of research than entrepreneurial expectation alone.…”
Section: Literature Reviewmentioning
confidence: 99%